Data for the calculation of an indicator of the comprehensiveness of conservation of useful wild plants - Khoury, Colin K.; Amariles, Daniel; Soto, Jonatan Stivens; Díaz, Maria Victoria; Sotelo, Steven; Sosa, Chrystian C.; Ramírez Villegas, Julián Armando; Achicanoy Estrella, Harold Armando; Castañeda Álvarez, Nora P.; León, Blanca; Wiersema, John H. (Elsevier, 2019)
The datasets and code presented in this article are related to the research article entitled “Comprehensiveness of conservation of useful wild plants: an operational indicator for biodiversity and sustainable development targets”1. The indicator methodology includes five main steps, each requiring and producing data, which are fully described and available here. These data include: species taxonomy, uses, and general geographic information (dataset 1); species occurrence data (dataset 2); global administrative areas data (dataset 3); eco-geographic predictors used in species distribution modeling (dataset 4); a world map raster file (dataset 5); species spatial distribution modeling outputs (dataset 6); ecoregion spatial data used in conservation analyses (dataset 7); protected area spatial data used in conservation analyses (dataset 8); and countries, sub-regions, and regions classifications data (dataset 9). These data are available at http://dx.doi.org/10.17632/2jxj4k32m2.1. In combination with the openly accessible methodology code (https://github.com/CIAT-DAPA/UsefulPlants-Indicator), these data facilitate indicator assessments and serve as a baseline against which future calculations of the indicator can be measured. The data can also contribute to other species distribution modeling, ecological research, and conservation analysis purposes.